The Impact of Peritoneal Dyalisis on the Family Life of Children with Chronic Kidney Disease - Lomba, Maria de Lurdes Lopes de Freitas (2014)
The CKD consists of the gradual and irreversible loss of the renal function. In Europe, the incidence of CKD cases extends from 4 to 7 per million in the population under 15 years old. Treatment: Initially: adequate protein and caloric intake, maintenance of the blood pressure levels and vitamin supplies. On long-term: renal transplant. It involves a lenghty process and until it is achieved, the alternative lies in dialysis. The PD allows the survival of the child but the care needed, in particular the achievement of PD at home, is complex and requires the family to adopt the role of a primary caregiver.